364 Efficacy of niraparib therapy in patients with newly diagnosed advanced ovarian cancer by brcawt status: prima/ENGOT-OV26/GOG-3012 study. (4th December 2020) - Braicu, Elena Ioana; Pothuri, Bhavana; Pérez-Fidalgo, Jose Alejandro; O'malley, David; Honhon, Brigitte; Graybill, Whitney; Fabbro, Michel; Dahlstrand, Hanna; Gupta, Divya; Monk, Bradley J
Abstract : Introduction/Background: Niraparib is a poly(ADP-ribose) polymerase inhibitor approved for maintenance treatment of patients with newly diagnosed advanced or platinum-sensitive, recurrent ovarian cancer (OC). Niraparib is also approved in the United States for the treatment of patients with OC who received ≥3 lines of therapy and whose cancer is either BRCA mutated or homologous recombination deficient (HRd) platinum-sensitive disease. The PRIMA/ENGOT-OV26/GOG-3012 trial showed that niraparib significantly improves progression-free survival (PFS) in patients with newly diagnosed advanced OC that responded to first-line platinum-based chemotherapy (hazard ratio, 0.62; 95% CI, 0.50–0.76). Here we report the efficacy of niraparib in patients by BRCA wild-type (BRCAwt) status. Methodology: This double-blind, placebo-controlled, phase 3 trial evaluated niraparib in patients with newly diagnosed, advanced, high-grade serous or endometrioid ovarian, primary peritoneal or fallopian tube cancer with a complete response (CR) or partial response (PR) to first-line platinum-based chemotherapy. Patients were stratified by best response to the first-line chemotherapy (CR/PR), receipt of neoadjuvant chemotherapy (yes/no), and homologous recombination status (deficient/proficient and not determined). Patients were randomised 2:1 to receive either niraparib or placebo once daily. The primary endpoint of PFS, assessed by blinded independent central review, was analysed using a stratified log-rank test and Cox proportional hazards model and hierarchically tested in HRd patients, then the overall population. BRCA and HRd status were determined by tumour samples at screening via the myChoice® test (Myriad, Salt Lake City, Utah). The prespecified BRCAwt subgroup PFS analysis was performed using a stratified log-rank test and Cox proportional hazards model and using Kaplan-Meier methodology. BRCAwt subgroups included the intention-to-treat/BRCAwt (all patients who were homologous recombination not determined [HRnd]/BRCAwt, HRd/BRCAwt, and homologous recombination proficient [HRp]/BRCAwt); subgroup analyses on the HRd/BRCAwt and HRp/BRCAwt were performed. Results: Of 733 randomised patients, 473 (64.5%) had BRCAwt tumours (74 patients had unknown BRCA status). Of these 473, 150 (31.7%) had HRd/BRCAwt tumours, 249 (52.6%) had HRp/BRCAwt tumours, and 74 (15.7%) had HRnd/BRCAwt tumours. Niraparib-treated patients with BRCAwt tumours had a clinically meaningful PFS benefit regardless of homologous recombination status (table 1 ). Conclusion: Niraparib improved PFS when utilised as maintenance therapy after front-line treatment of OC in patients with BRCAwt tumours, including in the most difficult to treat subgroup of patients with BRCAwt and HRp tumours. Disclosures: Dr. Braicu reports honoraria from AstraZeneca, Tesaro, GSK, Roche Pharma, Clovis and MSD; consulting or advisory roles at AstraZeneca, Tesaro, GSK, Roche Pharma, Clovis, MSD, Abbvie, Eisai, Immunogen, Takeda; institutional research funding from Roche Diagnostics and Takkeda; and travel, accommodation and expenses from Astra Zeneca, RochePharma, Clovis, and MSD. Dr. Pothuri reports grants, personal fees and non-financial support from GSK; Advisory Board fees from AstraZeneca and Clovis Oncology. Dr. Alejandro Perez-Fidalgo reports speaker fees from GSK, AstraZeneca, Clovis, and Roche; advisory fees from GSK, AstraZeneca, Clovis, Abilify Pharma, Clinigen, Roche, and Amgen; grant from GSK; and travel fees from AstraZeneca and Roche. Dr. O'Malley reports personal fees from Immunogen, Eisai, Agenus, GSK : Consultant/Advisory Board for Clovis, Ambry, Abbvie, Janssen/J&J, Regeneron, Novacure, Myraid Genetics, Tarveda, Amgen, VentiRx, Array Biopharma, EMD Serono, Ergomed; Steering committee for Genentech/Roche and Merck; Institutional funding from Ajinomoto Inc, Ludwig Cancer Research, Stemcentrx, Inc, CERULEAN PHARMA, GOG Foundation, BMS, Serono Inc, TRACON Pharmaceuticals, Yale University, New Mexico Cancer Care Alliance, INC Research, Inc., Inventiv Health Clinical, Iovance Biotherapeutics, Inc, and PRA International. Dr. Graybill reports personal fees from GSK. Dr. Dahlstrand reports personal fees from AstraZeneca and Roche. Dr. Monk reports consulting and advisory role at Merck, GSK, Roche/Genentech, AstraZeneca, Advaxiz, Cerulean Pharma, Amgen, Immunogen, NuCana BioMed, Clovis Oncology, Pfizer, Mateon Therapeutics, Precision Oncology, Perthera, Abbvie, Myriad Pharmaceuticals, Incyte, VBL Therapeutics, Takeda, Samumed, Oncomed, OncoSec, ChemoID, Geistlich Pharma, Eisai and Chemocare; Speakers' bureau at Roche/Genentech, AstraZeneca, Janssen, Clovis Oncology and GSK; Honoraria from Merck, GSK, Roche/Genentech, AstraZeneca, Advaxis, Immunogen, NuCana BioMed, Clovis Oncology, Pfizer, Mateon Therapeutics, Precision Oncology, Pethera, Abbvie, Myriad Pharmaceuticals, Incyte, Janssen, Amgen, Genmab, Samumed, Takeda, VBL Therapeutics, Puma Biotechnology, Immunomedics, Conjupro Biotherapeutics, Agenus, OncoQuest, ChemoID, Geistlich Pharma, Eisai and Chemocare; and Research funding from Novartis, Amgen, Genentech, Lilly, Janssen, Array BioPharma, GSK, Morphotek, Pfizer, Advaxis, AstraZeneca, Immunogen, Regeneron, and Nucana. Drs. Honhon and Fabbro have nothing to disclose. Dr. Gupta is an employee of GlaxoSmithKline.